Team experiential learning through community services delivery at private drug rehabilitation centres by university students: focus group discussion - Mohd Faisal, Nur Amni 'Afifah; Ab Rahman, Norny Syafinaz; Mohamed Nazar, Nor Ilyani; Ridzwan, Irna Elina; Zin, Che Suraya; Turner, Christopher John; Mohd Taufek, Nor Hidayah (IIUM Press, 2024)
Introduction: Substance abuse problem necessitates comprehensive community responsibility including university students to assist with the recovery of the marginalised population. This study aimed to investigate perception and experiences addressing team experiential learning as well as barriers to learning perceived by university students who provided community services at private drug rehabilitation centres. Materials and methods: Six focus group discussions were conducted with graduated and undergraduate pharmacy students who provided community services in private drug rehabilitation centres. A guide was used to explore students’ experiences, challenges encountered, and perceived learnings. Data were extracted from interview transcripts, sorted, and coded using Atlas.ti® version 9 and subjected to thematic analysis. Results: The themes identified according to the scope of learning experience were (1) contribution of knowledge, (2) positive interaction, (3) application of interprofessional learning, and (4) appreciation of team experiential practice. Themes emerged under the scope of gaps and barriers were (1) initial negative perception, (2) communication barriers, (3) technical problems and (4) difficulties in coping with behaviours. For perceived learnings, themes identified were (1) enhanced confidence and skills, (2) contact with reality, and (3) increased empathy. Conclusion: Team experiential learning in community service for marginalised population provided students with opportunities to directly contribute to the community and improved their learning.